Transforming Arabic Poetry Learning Through AR OASIS: Development Of An Augmented Reality Instructional Module - Mohd Feham Md. Ghalib; Wan Rusli Wan Ahmad; Muhammad Sabri Sahrir; Mohd Fauzi Abdul Hamid; Muhammad Akmal Zolmaily; Mohamad Lukman Al Hakim Md. Noor (Ijaz Arabi Journal of Arabic Learning, 2026)
Augmented Reality (AR) has attracted increasing attention in educational research for its potential to enhance learning through immersive, multimodal experiences; however, its application in Arabic poetry learning remains underexplored. This study aims to analyse pedagogical challenges and learner needs in studying Arabic poetry, to design an AR-based instructional module grounded in instructional design and multimedia learning principles, and to develop the proposed module through the AR Oasis application. A quantitative research design employing a survey-based needs analysis was implemented with five undergraduate Arabic learners. Descriptive statistical analysis revealed that difficult vocabulary constituted the most critical challenge (100%), followed by complex grammar, lack of historical and cultural context, and difficulty in visualising poetic imagery (each at 80%), while low interaction and boredom were reported by 40% of participants. Learners demonstrated a strong preference for visual explanations (100%), contextual and digital learning approaches (80%), and multimodal AR content integrating text, images, audio, video, animation, and three-dimensional objects (100%). From a usability perspective, page-flipping navigation (100%), combined icon–text menus (80%), and mobile-first design (60%) were strongly favoured. These findings confirm that the challenges of Arabic poetry learning are not purely linguistic but are deeply tied to visualisation, contextualisation, and learner engagement. The study contributes to the emerging field of immersive literary learning by providing empirically grounded design requirements for AR-based Arabic poetry instruction. Although constrained by a small sample size, the findings offer a robust foundation for future large-scale experimental and longitudinal research on AR-supported literary education.